Uma nova abordagem à filtragem de harmônicos através de dispositivos eletromagnéticos - Belchior, Fernando Nunes (2006)
Nowadays, the quality of the electric energy emerges as an important subject for both the consumers and the power utilities. In this context, it is recognized the existence of national and international guide lines towards the establishment of boundary or reference values for the power indexes so as to guarantee the desired standard of voltage quality. Amongst these indicators, the harmonic distortions appear as a quite important matter and the mitigation techniques to eliminate or to reduce the level of distortions have been largely discussed in the literature. The use of classical passive and active filters are the most traditional solutions, however, some authors have pointed the possibility of using a different approach based on electromagnetic devices. Focusing this subject, this thesis investigates the use of two distinct filtering devices for harmonic filtering. The first proposal is related to the well known zero sequence harmonic components and the second to the positive and negative components. The work considers the electromagnetic filter physical principles, modeling, computational implementation, investigation of ideal and non ideal operational conditions, laboratory scale prototypes and validation tests.